Gastro-protective effects of methanol extract of Tephrosia calophylla - Ramesh, C; Prameela Rani, A. (Journal of Drug Delivery and Therapeutics, 2018)
Objective: The present research work was designed to investigate gastro protective potentials of methanol extract of Tephrosia calophylla.Methods: The aerial parts of Tephrosia calophylla were dried under shade, powdered and deffated with petroleum ether and then marc left over was subjected to methanol extraction using soxhlet apparatus. Antiulcer activity of methanol extract was determined against stress induced and aspirin induced ulcers in experimental animal models. The total number of ulcers formed, ulcer index, percentage inhibition, ulcerated area, protected area, pH and Total acidity were parameters in the study.Results: Methanol extract of Tephrosia calophylla have significantly reduced the total number of ulcers formed, ulcer index, ulcerated area and total acidity in therapeutic groups compare to vehicle control and there by significantly increased percentage inhibition of ulcers and protected area which was evident by significant rise in pH of gastric content. The effect of extracts was dose dependent and results were comparable to that of standard drug omeprazole.Conclusion: The results obtained from the present work suggest that the methanol extract of Tephrosia calophylla possess significant anti-ulcer potentials against experimentally induced ulcers in albino rats.Keywords: Tephrosia calophylla, Anti ulcer activity, Ethanol, Aspirin Ulcer index, pH, total acidity, Percentage inhibition and percentage of protected area.